PENGARUH MEDIA PUZZLE DRAG AND DROP BERBASIS CANVA TERHADAP KEMAMPUAN MENGENALI ELEMEN CERITA RAKYAT SISWA KELAS III SD - Eka Lussy Sulistiyowati; Bahauddin Azmy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesian language learning in elementary schools, particularly in folklore instruction, still faces problems related to students’ low ability to understand folklore elements, including characters, plot, setting, and moral values. This condition is caused by the dominant use of conventional teaching methods that provide limited student engagement. Therefore, there is a need for interactive learning media to support meaningful learning (deep learning). This study aimed to determine whether there is an effect of using Canva-based drag-and-drop puzzle media on third-grade students’ ability to understand folklore elements. This study used a posttest-only control group design using a quantitative, quasi-experimental methodology. Students at SDN Rungkut Menanggal I/528 Surabaya in the third grade served as the participants. They were split into two groups: an experimental group and a control group. A posttest was used to gather the data, and an independent samples t-test was used for analysis. With a significance value of less than 0.05, the results demonstrated a substantial difference in posttest scores between the experimental and control groups. Therefore, it can be concluded that Canva-based drag-and-drop puzzle media have a significant effect on improving students’ ability to understand folklore elements.